Risk management and its implications on household incomes - Peron A. Collins-Sowah; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2019)
The subject of risk in agricultural production is very pertinent and touches on various aspects such as investments, food security, income levels of farmers, and market stability. Unmanaged, risks can have profound impacts on the agricultural sector and at the same time severely hamper long-term economic growth and poverty reduction efforts. Furthermore, risk management by farm households are multifarious with each having different cost and benefit implications. Using empirical data from a nationally representative farm household survey in Senegal, we evaluated the effect of different risk management strategies employed by farm households on agriculture income and dispersions around incomes. We achieve this by employing a Multinomial Endogenous Switching Regression model and a Moment-Based Approach. We find mix results of the impact of risk management on agriculture incomes. The use of risk mitigation and transfer significantly reduces agriculture incomes while risk coping strategies significantly increases agriculture incomes. Risk mitigation strategies were observed to be associated with opportunity costs relating to income loss and likely inefficient resource allocations. On the contrary, the reduced agricultural incomes observed with the use of risk transfer might be related moral hazard problems such that insurance policy holders do not take care or expend less effort in their production activities. We also find that risk management strategies significantly reduce dispersions around agriculture incomes with risk transfer producing the largest effect. Furthermore, the effect of risk transfer strategies on dispersions around agriculture incomes is reduced when combine with other strategies. For the other risk management strategies, we find that when used in combinations, the dispersion reduction effect is greatly enhanced.
Keywords: 330; Risk management; strategies; dispersion; multinomial; mitigation; transfer; coping